Second Life for the Psalms - Papanikolau, Dēmētrēs ca. 20./21. Jh. (The Biblical archaeology review, 2022)
Many psalms enjoyed a second life in postclassical and medieval Greek epigraphy (inscriptions). Hundreds of Greek inscriptions from the first to 15th centuries A.D. preserve verses—or entire psalms—taken from the Book of Psalms of the Septuagint, the Greek translation of the Hebrew Bible (Old Testament) compiled in the third and second centuries B.C. Alongside […]